PENGARUH PEMIJATAN AKUPRESUR PADA TITIK ST25 DAN CV6 TERHADAP PENINGKATAN NAFSU MAKAN PADA BALITA USIA 12-24 BULAN DI PMB BIDAN LIANA - Widiatami, Tiara; Isnina, Isnina; Florida, Melan Jeyn Putri (Jurnal Borneo Cendekia, 2023)
ABSTRACT The condition of reduced appetite in toddlers is a psychological disorder of growth and development which is characterized by impaired growth and development. Basic Health Research (Riskesdas) in 2018, shows that nationally the prevalence of underweight and very underweight toddlers is 17.7%, the prevalence of short and very short toddlers is 30.8% and the prevalence of very thin and wasted toddlers is 10.2%. Meanwhile, based on the results of the 2017 Nutritional Status Monitoring (PSG), it shows that 3.8% of children under five in Indonesia have poor nutritional status and 14% of children under five have malnutrition, the percentage of underweight/undernourished (malnutrition). In the toddler group as much as 17.8%, higher than the group under five years (baduta) which was 14.8%. Central Kalimantan province is one of the provinces with the highest cases of malnutrition in Indonesia, cases of malnutrition in Central Kalimantan province in 2018 were 5.50%. In West Kotawaringin Regency, the percentage of malnutrition and malnutrition among children under five is 2.3%. Several acupressure therapy points that are scientifically proven to increase toddlers' appetite are the ST36 (Zusanli), CV12 (Zhongwan), SP3 (Taibai), SP6 (San Yinjio), then the ST25 (Tian Shu) point which is located between the left and right of the umbilicus. and CV6 (Qi Hai) which is located below the umbilicus. The aim of this research is to determine massage therapy using acupressure techniques in increasing appetite in toddlers. This research is a quantitative research using a Quasi Experiment method with a Non-Randomized Control Group Pretest-Posttest design. There was an increase in body weight in toddlers with acupressure and education compared to the group given education without acupressure. Keywords: Acupressure, ST 25, CV6, Appetite, Toddlers